2000
DOI: 10.1109/65.819175
|View full text |Cite
|
Sign up to set email alerts
|

Multicast routing algorithms and protocols: a tutorial

Abstract: Multicasting is the ability of a communication network to accept a single message from an application and to deliver copies of the message to multiple recipients at different locations. Recentlv. there has been an exolosion of research literature on < .multicast communication. This ulticasling is the ability of a communication network to acccpt a single message from an application and to dclivcr copies of the mcssagc to multiple recipients at different locations. One of the cliallcngcs is to minimize tho amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(77 citation statements)
references
References 34 publications
0
77
0
Order By: Relevance
“…The goal of algorithm is to schedule as many destinations as possible to receive the multicast packet in each transmission trial. The MDSA operates in two modes, the initial mode and the maximum mode 4 . It simply starts scheduling the multicast packet in the initial mode by finding the earliest time slot at which the multicast packet can be scheduled.…”
Section: Maximum-destination Scheduling Algorithm [28]mentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of algorithm is to schedule as many destinations as possible to receive the multicast packet in each transmission trial. The MDSA operates in two modes, the initial mode and the maximum mode 4 . It simply starts scheduling the multicast packet in the initial mode by finding the earliest time slot at which the multicast packet can be scheduled.…”
Section: Maximum-destination Scheduling Algorithm [28]mentioning
confidence: 99%
“…The second algorithm uses the single packet transmission approach and it delivers the multicast packet to all the receivers in one time slot, and is therefore called the no-partition algorithm. Based on the simulation results, the authors observed that the MDSA achieves lower 4 These names are given for the sake of explaning the operation on the MDSA only and they were not used in [28] packet delay than both the greedy and the no-partitioning algorithms.…”
Section: Maximum-destination Scheduling Algorithm [28]mentioning
confidence: 99%
See 1 more Smart Citation
“…Multicast is a point-to-multipoint communication that a node sends data to multiple destinations [4,13]. There are many multicast applications, such as news feeds, video distribution, multimedia conferencing, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…There are many multicast applications, such as news feeds, video distribution, multimedia conferencing, and so on. It is a challenging job to implement multicast in Wide Area Networks (WANs) due to high complexity of multicast routing [10,13]. Multicast routing is to find a tree rooted from the source and connecting all the destinations.…”
Section: Introductionmentioning
confidence: 99%